2014
DOI: 10.1016/j.socscimed.2014.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Victory for volunteerism? Scottish health board elections and participation in the welfare state

Abstract: This paper presents findings from a multimethod study of pilot elections held to choose members of health boards in the National Health Service in Scotland. We begin by proposing that much current public involvement practice is dominated by a volunteerist model, in which members of the public with time and skills to offer play essentially supportive and non-challenging roles within health care organizations. This model contrasts sharply with the adversarial, political model of electoral democracy. Nonetheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Recent research in Scotland has highlighted that building on existing 'volunteerism' in participation provides a useful way of engaging and involving patients and the public in local decision-making and this needs to be done by identifying whether particular groups are marginalised or excluded rather than being classed as unrepresentative. 176 None of our case studies had developed ways of measuring or systematically identifying the benefits or otherwise of PPEI. There was no attempt to build in processes for monitoring the impact or costs of PPEI.…”
mentioning
confidence: 99%
“…Recent research in Scotland has highlighted that building on existing 'volunteerism' in participation provides a useful way of engaging and involving patients and the public in local decision-making and this needs to be done by identifying whether particular groups are marginalised or excluded rather than being classed as unrepresentative. 176 None of our case studies had developed ways of measuring or systematically identifying the benefits or otherwise of PPEI. There was no attempt to build in processes for monitoring the impact or costs of PPEI.…”
mentioning
confidence: 99%
“…For example, 91% of elected board members surveyed indicated that they would support a decision they believed to be right, even if it were opposed by the community, and 30% felt that their input to the board was not strongly influenced by the people in the community (Lewis et al ., ). The Scottish study found that while elected members expressed some confusion about their dual accountability, most accepted that they were primarily reporting to central government and adopted similar perceptions of their role to those of previously appointed members (Greer et al , ). In the New Zealand case, Tenbensel et al (, p. 245) argued that “responsiveness to central government strategies has far outweighed the representation of local communities in decision making.”…”
Section: Resultsmentioning
confidence: 99%
“…Both NHS Fife and NHS D&G have very large white majorities, and there was only one non‐white candidate (two did not state their ethnicity), so it is not obvious that ethnic minorities were underrepresented. But the elected did seem to be better‐educated than the population as a whole, with more formal qualifications than is typical among the population (Greer et al , p. 23).…”
Section: Authorizationmentioning
confidence: 99%
“…In NHS systems it can mean elections to local health organizations. This has been tried in England (Allen et al ), New Zealand (Gauld ), some Canadian provinces (Eakin ; Lomas ), and – in 2010 – two Scottish Health Boards (Greer et al ).…”
Section: Introductionmentioning
confidence: 99%